INNOVATIVE METHODS OF TEACHING VISUAL ARTS USING DIGITAL TECHNOLOGIES FOR GRADES 5–7 - Xamidova Dildora Muhiddin qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article explores innovative methods for teaching visual arts to students in grades 5–7 using digital technologies in general secondary schools. It examines the role of interactive lessons, multimedia applications, and digital drawing tools in enhancing students’ creativity, artistic skills, and visual literacy. The study highlights the effectiveness of digital technologies in promoting engagement, individualized learning, and collaborative art projects.